2021
DOI: 10.3390/pr9112006
|View full text |Cite
|
Sign up to set email alerts
|

A Polyphasic Characterisation of Tetradesmus almeriensis sp. nov. (Chlorophyta: Scenedesmaceae)

Abstract: The microalga Tetradesmus almeriensis, previously known as Scenedesmus almeriensis, has been isolated and cultivated as a highly productive, fast-growing strain known as a natural source of different products of commercial interest, including bioactive compounds such as lutein. This strain produces up to 40 g·m−2·day−1 of lutein under optimal conditions and is highly recommendable for outdoor production in temperate and warm climates, showing maximal performance at temperatures up to 35 °C with no photo-inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The oval or ellipsoidal cells are typical traits of the genus Scenedesmus (Tsarenko and John, 2011). Furthermore, the phylogenetic analysis using rbcL and ITS sequences revealed that T. almeriensis shows a monophyletic relationship with Scenedesmus species (Turiel et al, 2021). We confirmed the same phylogenetic relationship using ITS1-5.8S-ITS2, rbcL, and tufA genes (Supplementary Figure 6); hence, we suggest transferring T. almeriensis CCAP 276/24 to the genus Scenedesmus as follows.…”
Section: Taxonomic Issues In the Genus Tetradesmussupporting
confidence: 77%
See 3 more Smart Citations
“…The oval or ellipsoidal cells are typical traits of the genus Scenedesmus (Tsarenko and John, 2011). Furthermore, the phylogenetic analysis using rbcL and ITS sequences revealed that T. almeriensis shows a monophyletic relationship with Scenedesmus species (Turiel et al, 2021). We confirmed the same phylogenetic relationship using ITS1-5.8S-ITS2, rbcL, and tufA genes (Supplementary Figure 6); hence, we suggest transferring T. almeriensis CCAP 276/24 to the genus Scenedesmus as follows.…”
Section: Taxonomic Issues In the Genus Tetradesmussupporting
confidence: 77%
“…For instance, T . almeriensis Turiel, Garrido-Cardenas, Gómez-Serrano, Acién, Carretero-Paulet & S.Blanco (the reference strain CCAP 276/24), which was reported as a new species in the genus Tetradesmus , displays oval or ellipsoidal cells without acuminate cell poles rather than spindle cells ( Turiel et al., 2021 ). The oval or ellipsoidal cells are typical traits of the genus Scenedesmus ( Tsarenko and John, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations